Impact of the diagnostic changes to post-traumatic stress disorder for DSM-5 and the proposed changes to ICD-11. (September 2014) - O'Donnell, Meaghan L.; Alkemade, Nathan; Nickerson, Angela; Creamer, Mark; McFarlane, Alexander C.; Silove, Derrick; Bryant, Richard A.; Forbes, David
Abstract : Background: There have been changes to the criteria for diagnosing post-traumatic stress disorder (PTSD) in DSM-5 and changes are proposed for ICD-11. Aims: To investigate the impact of the changes to diagnostic criteria for PTSD in DSM-5 and the proposed changes in ICD-11 using a large multisite trauma-exposed sample and structured clinical interviews. Method: Randomly selected injury patients admitted to four hospitals were assessed 72 months post trauma ( n = 510). Structured clinical interviews for PTSD and major depressive episode, as well as self-report measures of disability and quality of life were administered. Results: Current prevalence of PTSD under DSM-5 scoring was not significantly different from DSM-IV (6.7% v. 5.9%, z = 0.53, P = 0.59). However, the ICD-11 prevalence was significantly lower than ICD-10 (3.3% v. 9.0%, z =–3.8, P <0.001). The PTSD current prevalence was significantly higher for DSM-5 than ICD-11 (6.7% v. 3.3%, z = 2.5, P = 0.01). Using ICD-11 tended to show lower rates of comorbidity with depression and a slightly lower association with disability. Conclusions: The diagnostic systems performed in different ways in terms of current prevalence rates and levels of comorbidity with depression, but on other broad key indicators they were relatively similar. There was overlap between those with PTSD diagnosed by ICD-11 and DSM-5 but a substantial portion met one but not the other set of criteria. This represents a challenge for research because the phenotype that is studied may be markedly different according to the diagnostic system used.